Mechanical Properties of Minerals in Daejeon Granite According to Depths by Dynamic Ultra-micro Hardness - Choi, J.; Shin, J.; Jang, Hyong Doo; Kang, S. (Korean Society for Rock Mechanics, 2017)
The hardness and mechanical properties of the minerals in the Daejeon granite according to depths were investigated by indentation test, load-unload test, and cycle test of dynamic ultra-micro hardness. As a result of the tests, it was possible to classify into three mineral groups (Group-1, -2, -3). The Martens hardness was not significantly different between 41 m and 223 m depths in three mode tests. Nevertheless, they showed in the order of a cycle test < load-unload test < indentation test. Considering the average Martens hardness, elastic modulus, and indentation work for each mineral group, their boundaries were relatively clear. In conclusion, A relatively accurate hardness of minerals can be obtained by three mode tests of dynamic ultra-micro hardness. In addtion, it was possible to characterize the elastic modulus and the elastic-plastic properties of the minerals from the load-unload and cycle tests.